Carroll's pyramid of CSR: taking another look - Archie B. Carroll (International Journal of Corporate Social Responsibility (JCSR), 2016)
In this review article, the author takes another look at the well-known Carroll's Pyramid of Corporate Social Responsibility (CSR). In this article, he comments on the framework's popular useage and then presents a summary of the four-part definitional framework upon which the pyramid was created. He then comments on several characteristics of the model that were not emphasized when initially published: ethics permeates the pyramid; tensions and tradeoffs inherent; its' integrated, unified whole; its' sustainable stakeholder framework, and; its' global applicability and use in different contexts. The article concludes by looking to the future.
Keywords: 650; Corporate Social Responsibility; Ethical Responsibility; Corporate Philanthropy; Legal Responsibility; Economic Responsibility